No-tillage, surface residue retention, and cover crops improved San Joaquin Valley soil health in the long term - Jeffrey P. Mitchell; Shannon B. Cappellazzi; Rad Schmidt; Jessica Chiartas; Anil Shrestha; Don Reicosky; Howard Ferris; Xiaoke Zhang; Teamrat A. Ghezzehei; Samuel Araya; Courtland Kelly; Steven J. Fonte; et al. (California Agriculture)
A long-term annual crop study in Five Points, California, shows that the combined use of no-tillage, surface residue retention, and cover crops improves soil health compared to conventional practices common to the region. Several chemical, biological, and physical soil health indicators were improved when these practices were combined. Our data suggest that farmers stand to gain multiple synergistic benefits from the integrated use of these practices by increasing soil structural stability, water infiltration and storage, and agroecosystem biodiversity, and improving the efficiencies of the carbon, nitrogen, and water cycles of their production systems.